Feasibility Study on IPMC Actuated Contractile Water Jet Thruster Body Contraction - Shaari, Muhammad Farid; Samad, Z.; Othman, M. H.; Marwah, O.M.F. (EDP Sciences, 2016)
This research was conducted to investigate the feasibility of Ionic Polymer Metal Composite (IPMC) as the actuator for Contractile Water Jet Thruster (CWJT). The thrust that generated from the accelerated volume of ejected fluid depends on the IPMC actuator contraction performance. During this investigation, the variation of contraction frequency and nozzle aperture influence on the body deformation was carried out. The results of the experiments exhibit that the body contraction decreased tremendously from 0.05 Hz to 0.15 Hz. The body contraction has no apparent decrement for more than 0.15 Hz of contraction frequency. Besides, larger nozzle aperture has relatively more body contraction than smaller nozzle aperture. These results show that the fixed actuation force and the contraction frequency have a significant influence on the CWJT body contraction.